Factors that influence career decision-making among elite athletes - Fogarty, G. J.; McGregor-Bayne, H. (Australian Journal of Career Development, 2008)
A common belief about elite athletes is that they invest so much effort into the pursuit of their athletic careers that they fail to develop good career decision-making skills. Recent findings challenge that belief. The present study investigated career decision-making difficulties among 117 elite Australian athletes. Participants completed adapted versions of the Career Decision-Making Difficulties Questionnaire, the Athlete Identity Measurement Scale, the Career Decision-making Self-efficacy Short Form, and the Work Locus of Control Scale. These elite athletes showed no evidence of career decision-making difficulties. Combinations of this set of variables accounted for 35% of the variance in decision status and 20% of the variance in career decision-making difficulties. Career decision-making self-efficacy was a major contributor in both instances. Internal locus of control was also identified as a desirable characteristic in the context of career decision-making. The implications of these findings are discussed.